Chitosan-Bentonite crosslinked film as indicator for copper (II) ions adsorption - Osman, Nurul Huda; Mazu, Nurul Najiha; Liew, Josephine Ying Chyi; Ramli, Muhammad Mahyiddin; Mohd Abdull Majid, Mohammad Abdull Halim; Mazlan, Hazeem Ikhwan (EDP Sciences, 2021)
This paper reports on chitosan/bentonite crosslinked (ChB-ECH) film for removal of Cu (II). The effects of chitosan/bentonite ratio on the removal percentage were studied along with the effect of different Cu (II) concentration and the contact time on the film adsorption capacity, qt. The electrical properties of the film are studied, before and after the adsorption occurred, by using impedance spectroscopy for different parameters such as DC conductivity, the complex dielectric constants (ε′ and ε″) and complex electrical modulas (M′ and M″). The results showed that the chitosan/bentonite ratio of 3:1 produces highest removal percentage at 29%, while the contact time of 120 minutes was found to be optimum. An increment in the DC conductivity of the ChB-ECH film's was observed up to 10−7 S/cm as the removal percentage of film increased. The film with the highest Cu (II) adsorb also showed the highest value for ε′ and ε″ while exhibiting non-Derby behavior. Shifting of peak amplitude of the M″ towards the higher frequency was also observed as the Cu (II) adsorption in the film increased. The results showed that all the electrical parameters can be utilized to determine the amount of adsorbed copper (II) in chitosan/bentonite film.